Discovery and SAR of muscarinic receptor subtype 1 (M1) allosteric activators from a molecular libraries high throughput screen. Part 1: 2, 5-Dibenzyl-2H-pyrazolo[4, 3-c]quinolin-3(5H)-ones as positive allosteric modulators. Issue 2 (15th January 2015) - Han, Changho; Chatterjee, Arindam; Noetzel, Meredith J.; Panarese, Joseph D.; Smith, Emery; Chase, Peter; Hodder, Peter; Niswender, Colleen; Conn, P. Jeffrey; Lindsley, Craig W.; Stauffer, Shaun R.
Graphical abstract: Abstract: Results from a 2012 high-throughput screen of the NIH Molecular Libraries Small Molecule Repository (MLSMR) against the human muscarinic receptor subtype 1 (M1 ) for positive allosteric modulators is reported. A content-rich screen utilizing an intracellular calcium mobilization triple-addition protocol allowed for assessment of all three modes of pharmacology at M1, including agonist, positive allosteric modulator, and antagonist activities in a single screening platform. We disclose a dibenzyl-2 H -pyrazolo[4, 3- c ]quinolin-3(5 H )-one hit (DBPQ, CID 915409) and examine N -benzyl pharmacophore/SAR relationships versus previously reported quinolin-3(5 H )-ones and isatins, including ML137. SAR and consideration of recently reported crystal structures, homology modeling, and structure–function relationships using point mutations suggests a shared binding mode orientation at the putative common allosteric binding site directed by the pendant N -benzyl substructure.